2005
DOI: 10.1161/01.res.0000162101.76263.8c
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Form of Short QT Syndrome (SQT3) Is Caused by a Mutation in the KCNJ2 Gene

Abstract: Abstract-Short QT syndrome (SQTS) leads to an abbreviated QTc interval and predisposes patients to life-threatening arrhythmias. To date, two forms of the disease have been identified: SQT1, caused by a gain of function substitution in the HERG (I Kr ) channel, and SQT2, caused by a gain of function substitution in the KvLQT1 (I Ks ) channel. Here we identify a new variant, "SQT3", which has a unique ECG phenotype characterized by asymmetrical T waves, and a defect in the gene coding for the inwardly rectifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
397
2
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 567 publications
(429 citation statements)
references
References 39 publications
18
397
2
12
Order By: Relevance
“…Mutations found in SQTS patients in the genes encoding potassium channels cause "gain of function," whereas mutations found in the alpha 1C subunit of the voltage-dependent L-type Ca + channel (CACNA1C), the beta 2b subunit of the voltage dependent Ca 2+ channel (CACNB2B) and the alpha2/delta subunit 1 of the voltage dependent Ca 2+ channel (CACNA2D1) cause "loss of function" (1,2). In 2005, we reported a mutation (D172N) in the strong inward rectifier K + channel protein (Kir2.1), which is coded by KCNJ2, in an SQTS patient: Functional characterization revealed that D172N shows an increased outward component of the inward rectifier current I K1 (3). Computer simulation demonstrated that D172N leads to a shortening of the QT interval and predisposes the heart to develop reentrant arrhythmias.…”
mentioning
confidence: 99%
“…Mutations found in SQTS patients in the genes encoding potassium channels cause "gain of function," whereas mutations found in the alpha 1C subunit of the voltage-dependent L-type Ca + channel (CACNA1C), the beta 2b subunit of the voltage dependent Ca 2+ channel (CACNB2B) and the alpha2/delta subunit 1 of the voltage dependent Ca 2+ channel (CACNA2D1) cause "loss of function" (1,2). In 2005, we reported a mutation (D172N) in the strong inward rectifier K + channel protein (Kir2.1), which is coded by KCNJ2, in an SQTS patient: Functional characterization revealed that D172N shows an increased outward component of the inward rectifier current I K1 (3). Computer simulation demonstrated that D172N leads to a shortening of the QT interval and predisposes the heart to develop reentrant arrhythmias.…”
mentioning
confidence: 99%
“…These currents are major determinants of action potential shape and are targets of antiarrhythmic drugs of class I (Na ϩ channel blockers), class III (K ϩ channel blockers), and class IV (Ca 2ϩ channel blockers) (75). These currents are also changed during various cardiac pathologies, e.g., long and short QT syndromes (30,41,52). Figure 4, A-E, illustrate the dependence of T critical and T spiral on the values of G Na , G Ca , G K1 , G Kr , and G Ks , respectively, expressed as percentages of their original values.…”
Section: Resultsmentioning
confidence: 99%
“…SQT2 is a mirror image of LQT1, with the mutation in KCNQ1 leading to a gain of function of I Ks in SQT2, but to a loss of function in LQT1. Similarly, a gain of function mutation in KCNJ2 was identified by Priori et al (2005) in a familial setting in an asymptomatic 5 year old child and 35 year old father who showed extremely short QT interval on ECG. Heterologous expression of the mutant channel showed that the genetic mutation caused a significant augmentation of I K1 responsible for abbreviation of action potential and QT interval.…”
Section: Molecular Genetics Of Sqtsmentioning
confidence: 93%
“…Similar to LQTS, SQTS is also genetically heterogeneous disease and thus far mutations in five different genes (Table 1) encoding different cardiac ion channels located on chromosome 7, 10, 11, 12 and 17 have been identified, and the corresponding syndromes have been termed SQT1 to SQT5 depending of chronology of discovery (Brugada et al, 2004;Bellocq et al, 2004;Priori et al, 2005;Antzelevitch et al, 2007). Interestingly, four of those genes are the same as those involved in LQTS; however mutations leading to SQTS have the net effect of increasing rather than decreasing depolarizing forces.…”
Section: Molecular Genetics Of Sqtsmentioning
confidence: 99%